2019
DOI: 10.1111/cea.13492
|View full text |Cite
|
Sign up to set email alerts
|

The influence of treatment in alpine and moderate maritime climate on the composition of the skin microbiome in patients with difficult to treat atopic dermatitis

Abstract: Background The skin microbiome, characterized by an overgrowth of Staphylococcus aureus, plays an important role in the pathogenesis of atopic dermatitis (AD). Multidisciplinary treatment in alpine climate is known for its positive effect on disease severity in children with AD and can result in a different immune response compared with moderate maritime climate. However, the effect on the composition of the skin microbiome in AD is unknown. Objective To determine the effect of treatment in alpine climate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
1
16
0
4
Order By: Relevance
“…In line with this, the relative abundances of Staphylococcus aureus were under the cut-off of 0.5% in all healthy controls and patients, in line with results from quantitative PCR (Table S3). Previous studies reported high levels of Staphylococcus aureus in skin lesions of adult patients with disease flare or severe AD, in contrast to nonlesional skin, which exhibits low to absent Staphylococcus aureus, similar to healthy skin (Baurecht H et al, 2018;Clausen ML et al, 2018;Francuzik W et al, 2018;Smits JPH et al, 2019;van Mierlo MMF et al, 2019;Zeeuwen P et al, 2017). Interestingly, a predominance of Staphylococcus epidermidis was already observed in patients with low to mild disease (Byrd AL et al, 2017), identical to AD patients from our cohort (mean EASI<5).…”
Section: Recent Work Has Demonstrated That Colonization Of the Skin Bsupporting
confidence: 82%
“…In line with this, the relative abundances of Staphylococcus aureus were under the cut-off of 0.5% in all healthy controls and patients, in line with results from quantitative PCR (Table S3). Previous studies reported high levels of Staphylococcus aureus in skin lesions of adult patients with disease flare or severe AD, in contrast to nonlesional skin, which exhibits low to absent Staphylococcus aureus, similar to healthy skin (Baurecht H et al, 2018;Clausen ML et al, 2018;Francuzik W et al, 2018;Smits JPH et al, 2019;van Mierlo MMF et al, 2019;Zeeuwen P et al, 2017). Interestingly, a predominance of Staphylococcus epidermidis was already observed in patients with low to mild disease (Byrd AL et al, 2017), identical to AD patients from our cohort (mean EASI<5).…”
Section: Recent Work Has Demonstrated That Colonization Of the Skin Bsupporting
confidence: 82%
“…A cohort in Southwest China (Li et al, 2018) revealed a positive association between the visits for eczema outpatients and airborne pollutants of NO 2 , SO 2 , and PM 10 , and another study from the Seoul Metropolitan Area (Kim et al, 2017) reported that a 10-U increase in PM 10 , NO 2 , and O 3 could aggravate same-day symptoms of AD. Alpine climate treatment led to a reduction in the Staphylococcus genus, further resulting in significant changes in the skin microbiome composition in AD children (van Mierlo et al, 2019). However, which strain of Staphylococcus was the dominant one in our present study and how much of the ratio between S. aureus and S. epidermidis could indicate the risk of inflammatory skin diseases, especially atopic eczema, need to be further investigated.…”
Section: A B C D F Ementioning
confidence: 60%
“…With the rapid development of national economy, environmental pollution is becoming a pressing issue. Skin, as the first line to interface with the air, is the target of various environmental stressors (Valacchi et al, 2012;Dong et al, 2019). Basic and clinical studies have provided growing evidence that airborne pollutants exacerbate skin aging (Vierktter et al, 2010;Ding et al, 2017) and even some chronic inflammatory skin diseases (Ahn, 2014;Pesce et al, 2015;Liu et al, 2018), which also exists when there is microbiome imbalance (He et al, 2006;Nielsen and Jiang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The ecosystems humans live in, which are affected by the status of biodiversity, climate, and urbanization, among other factors, shape the human skin microbiome [ 82 ]. Van Mierlo et al [ 56 ] investigated the influence of the alpine climate, characterized by lower pollution and allergen levels and increased UV radiation, on lesional and non-lesional skin of children with difficult-to-treat AD. After six weeks of alpine climate treatment, a significant shift in the general skin microbiome of AD lesions was observed.…”
Section: Extrinsic Influences Shaping the Skin Microbiomementioning
confidence: 99%